2012
DOI: 10.1088/1742-6596/395/1/012180
|View full text |Cite
|
Sign up to set email alerts
|

Sliding bubble dynamics and the effects on surface heat transfer

Abstract: An investigation into the effects of a single sliding air bubble on heat transfer from a submerged, inclined surface has been undertaken. Existing literature has shown that both vapour and gas bubbles can increase heat transfer rates from adjacent heated surfaces. However, the mechanisms involved are complex and dynamic and in some cases poorly understood. The present study utilises high speed, high resolution, infrared thermography and video photography to measure two dimensional surface heat transfer and thr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…By changing from rising bubbles to sliding ones, Maxworthy [9] performed one of the first studies of the dynamics of a bubble sliding under an inclined surface, explaining that sliding bubbles differed from free rising bubbles in that they only experienced a predominant buoyancy force [9,[26][27][28][29]. Depending on the angle of inclination of the upper wall and the bubble size, several behaviors of bubbles can be found: (i) bouncing for low angles of α < 5° [29], (ii) sliding for intermediate angles 5°< α < 80° [26,27,30], or (iii) steady bouncing of constant amplitude for high angles [18,31]).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…By changing from rising bubbles to sliding ones, Maxworthy [9] performed one of the first studies of the dynamics of a bubble sliding under an inclined surface, explaining that sliding bubbles differed from free rising bubbles in that they only experienced a predominant buoyancy force [9,[26][27][28][29]. Depending on the angle of inclination of the upper wall and the bubble size, several behaviors of bubbles can be found: (i) bouncing for low angles of α < 5° [29], (ii) sliding for intermediate angles 5°< α < 80° [26,27,30], or (iii) steady bouncing of constant amplitude for high angles [18,31]).…”
Section: Introductionmentioning
confidence: 99%
“…Particle Image Velocimetry PIV under three different angles of inclination (α=20°, 30°, and 40°) [26][27][28]. It has been shown that an increase of α and bubble db increased the bubble velocities [9,30,32]. In addition, the spatial and temporal evolution of the flow structures consisted of two distinct regions: (i) a near wake moving in close association with the bubble, forming a recirculation region after which fluid separated from this high-velocity region and was drawn towards the inclined surface.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Donnelly et al (2009Donnelly et al ( ), (2012 conducted experiments of bubble sliding in natural convection, which corroborated that assumption. Similarly, the bubble causing the greatest disruption in a forced convection thermal boundary layer is the one with the highest Reynolds number (large relative velocity and bubble diameter); this corresponds to the bubble just departing the injection or nucleation site.…”
Section: Stationary Bubble Near Wallmentioning
confidence: 54%